Особливості водно-хімічного режиму другого контуру атомних електричних станцій України - Коваленко, Т. П.; Матіко, Г. Ф. (СПДФО Марусич М. М., 2020)
The main sources of pollution of the working fluid of the secondary circuit of nuclear power plants (NPP) of Ukraine are considered in the work. Measures for improving the water chemistry conditions of NPP are presented. The authors proved that ensuring optimal physical and chemical properties of heat carrier will help to reduce corrosion damages of equipment and deposits on its surfaces.
Features of water chemistry conditions of the secondary circuit of nuclear power plants of Ukraine